Modes of dystopia and representations of the technique in "Abejas de cristal", by Ernst Jünger, and "La caja de las orquídeas", by Herbert Franke - García, Nicolás (Tropelías: Review of Literary Theory and Comparative Literature, 2022)
The combination of the extra-planetary adventure genre and the exemplary critical cognition of science fiction, that Herbert Franke’s La caja de las orquídeas develops, suits a particular type of vision of the technique which will have a partial correlation with a contemporary novel, also dystopian in orientation, such as Ernst Jünger’s Abejas de cristal. The following work will be devoted to deciphering possible convergences and discontinuities between two narrative works that expose the characteristic concerns of German literature of the atomic period.